Cross-linguistic categorization of throwing events: A behavioral approach - Wang, Haoshu (2017)
Research on cross-linguistic categorization reveals that there were universal principles constraining the categorization of motion events across languages, and variations only distributed in a limited range. However, this finding has not been widely verified across languages and semantic domains. In this paper, we will address whether the universal constraints exist in the cross-linguistic categorization of throwing events, with the data collected with a behavioral approach. We asked 79 adult native speakers of English(12 male, 17 female), Chinese(15 male, 15 female), and German(18 male, 12 female) to perform actions denoted by near-synonymous ‘throw’ verbs in their native languages. Then we coded the features of their actions and compared them across individuals and languages. The results support the finding of previous studies that event categorization is constrained across languages. In addition, the top-down approach we adopted in this study allowed us to capture the focal and extensional semantic range of each verb involved, which advanced our knowledge of event categories and different semantic representations of a class of near-synonyms.